Influence of neoadjuvant therapy on outcomes in patients with resectable carcinoma of esophagus and gastro‐esophageal junction from a tertiary cancer care center in India. Issue 7 (2nd March 2021) - Rao T., Subramanyeshwar; Raju, Kalidindi Venkata Vijaya Narsimha; Patnaik, Sujit Chyau; Reddy, Pratap; Saksena, Ajesh Raj; Rajappa, Senthil; Mallavarapu, Krishna Mohan; Santa, Ayyagari; Gudipudi, Deleep; Boleneni, Naren; Usofi, Zeeba; Gujjuru, Swathi; et al.
Abstract: Background and Objectives: The aim of this study is to compare the outcomes of neoadjuvant chemotherapy (nCT), neoadjuvant chemoradiotherapy (nCRT) followed by surgery to upfront surgery (surgery alone) in patients with resectable carcinoma of the esophagus (esophageal cancer [EC]), and gastro‐esophageal junction (GEJ) in a limited resource setting. Methods: A retrospective analysis of a prospectively maintained database was performed to identify patients (from January 2010 through December 2016) who underwent surgery for EC and GEJ cancers. Results: A total of 454 patients were included and categorized into the following groups: nCT ( n = 65), nCRT ( n = 152) and upfront surgery ( n = 237). Squamous cell carcinoma and adenocarcinoma accounted for two‐thirds and one‐third of the cases, respectively. nCRT group patients were also noted to have smaller tumors, lower margin positivity and a higher R0 resection rates. With a median follow up of 76 months (35–118 months) improved 5‐year overall survival was noted in nCRT group in comparison to nCT and upfront surgery groups (56.5% vs. 34% and 35%, respectively, p = .021). Conclusions: The results of our study demonstrate the beneficial effect of nCRT for patients with EC and GEJ in a limited resource setting. Further studies are required to analyze and promote the benefits of nCRT in limited‐resource settings.